THE ROLE OF PHYSICAL EDUCATION IN FORMING THE ATTITUDE OF ELEMENTARY SCHOOL STUDENTS TO MORAL VALUES THROUGH FOLK GAMES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article investigates the potential of traditional Uzbek folk games in shaping primary school pupils’ moral values within the context of physical education lessons. In modern pedagogy, fostering students’ ethical and cultural awareness is no less important than the academic curriculum. Through the integration of national games into physical education, it is possible to build children's sense of friendship, cooperation, mutual respect, justice, and patriotism.